Znaczenie bezpośrednich inwestycji zagranicznych dla rozprzestrzeniania się wiedzy, oceniane na podstawie zmian w produktywności czynników wytwórczych - Wachowska, Małgorzata (Wydawnictwo Uniwersytetu Wrocławskiego, 2007)
This paper analyses the effect of both inward and outward FDI on knowledge diffusion in a country. The main focus of the paper is on one of the methods of measurement of that effect which evaluates knowledge diffusion on the basis of positive relationship between FDI and increase in factor productivity. On the basis of the analysis done in this paper, it may be concluded that FDI significantly promote knowledge diffusion in both the host and home countries. It should be noted that estimates of strength and scope of that diffusion differ depending on whether the studies use macro or micro level data as well as whether they analyze cross-section or panel data.
Keywords: bezpośrednie inwestycje zagraniczne; wiedza; przepływ wiedzy